Procedural features of the institution of representation in criminal proceedings - Rohatynska, Nina (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article is devoted to the institution of representation in criminal proceedings. Theoretical aspects of the institution of representation in criminal proceedings are considered. Human rights and freedoms and their guarantees determine the content and direction of state activity. By its very nature, representation is one of the institutions of a democratic society, as it performs the most important civic function – protection of the rights and legitimate interests of citizens and legal entities. Obtaining legal aid allows each person, within the framework of criminal proceedings, to feel protected and to establish limits of communication with law enforcement agencies, prosecutor’s offices and the court. Therefore, the institution of representation in criminal proceedings occupies an important place among the problems of criminal procedural legislation and determines the procedural features of the status of persons who can represent the interests of the subjects of criminal proceedings. The content of the concept of legal aid as a basic human right and a necessary element of a fair, humane and effective justice system based on the rule of law is revealed. The range of persons who can participate in the consideration of a criminal case as representatives has been analyzed. Regarding subjects of criminal proceedings authorized to exercise representation, analyzing the current Code of Criminal Procedure of Ukraine shows that they have a rather complex branched structure with unstable differences in their procedural status.